2000
DOI: 10.1002/1097-4539(200009/10)29:5<365::aid-xrs441>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the zeolite and silicate content in detergent products by wavelength‐dispersive x‐ray fluorescence spectrometry

Abstract: A method was developed for the determination of zeolite and silicate in detergent products and raw materials by wavelength-dispersive x-ray fluorescence (WDXRF) spectrometry. Al, Si and Na were measured after fusion of the sample with a mixture of lithium tetra-and metaborate. The influence of the fusion conditions, the stability of the glass beads and calibrations using practical and calculated a values were studied. The WDXRF method was validated by analysing laundry detergent products and zeolite and sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…According to a whole set of attractive and useful cation exchange, catalytic, molecular sieves, sorption properties for many years, new applications and new directions of utilization have been sought for zeolites. Among the most important directions of the application, the following can be indicated as most interesting: as addition in asphalt production (Sengoz et al 2013;Topal et al 2014;Woszuk andFranus 2016, 2017;Woszuk 2018), civil engineering (Feng andPeng 2005;Tanijaya and Jardjito 2008;Markiv et al 2016;Linek et al 2018), in agriculture (Shi et al 2009;Ramesh and Reddy 2011;Eprikashvili et al 2016;Behzadfar et al 2017;Nakhli et al 2017), in detergent production (Van Dalen and Vooijs 2000;Sekhon and Sangha 2008;Fruijtier-Pölloth 2009;Ayele et al 2016), in medicine and pharmacy (among other as potential drug carriers) (Andronikashvili et al 2009;Pavelić and Hadzija 2010;Selvam et al 2014;Mohammadkhani et al 2016;Backova et al 2018;Kraljević Pavelić et al 2018;Krajišnik et al 2019), environmental protection andengineering (Maèala et al 2009;Wdowin et al 2014b;Burmańczuk et al 2015;Franus et al 2015;Ates and Akgül 2016;Czarna et al 2016), in cosmetology (Joughehdoust andManafi 2008), in food industry (Kuley et al 2012), in catalysis (Yilmaz and Müller 2009; Fig. 7 SEM micrographs of selected best synthesis of Na-A, N...…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…According to a whole set of attractive and useful cation exchange, catalytic, molecular sieves, sorption properties for many years, new applications and new directions of utilization have been sought for zeolites. Among the most important directions of the application, the following can be indicated as most interesting: as addition in asphalt production (Sengoz et al 2013;Topal et al 2014;Woszuk andFranus 2016, 2017;Woszuk 2018), civil engineering (Feng andPeng 2005;Tanijaya and Jardjito 2008;Markiv et al 2016;Linek et al 2018), in agriculture (Shi et al 2009;Ramesh and Reddy 2011;Eprikashvili et al 2016;Behzadfar et al 2017;Nakhli et al 2017), in detergent production (Van Dalen and Vooijs 2000;Sekhon and Sangha 2008;Fruijtier-Pölloth 2009;Ayele et al 2016), in medicine and pharmacy (among other as potential drug carriers) (Andronikashvili et al 2009;Pavelić and Hadzija 2010;Selvam et al 2014;Mohammadkhani et al 2016;Backova et al 2018;Kraljević Pavelić et al 2018;Krajišnik et al 2019), environmental protection andengineering (Maèala et al 2009;Wdowin et al 2014b;Burmańczuk et al 2015;Franus et al 2015;Ates and Akgül 2016;Czarna et al 2016), in cosmetology (Joughehdoust andManafi 2008), in food industry (Kuley et al 2012), in catalysis (Yilmaz and Müller 2009; Fig. 7 SEM micrographs of selected best synthesis of Na-A, N...…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The determination of zeolite and silicate in detergent products and in raw materials by WDXRF was also discussed. 317 A study of the effect of cationic polysaccharides on polydimethylsiloxane deposition onto hair via a surfactant-emulsified (shampoo) formulation was carried out using XRF directly as the diagnostic technique. 318 It was reported that the cationic charge level appeared to control the build up of silicone oil deposition after multiple shampooing treatments.…”
Section: Industrialmentioning
confidence: 99%